Cystoid macular oedema following cataract extraction in patients with diabetes. - Pollack, A. (1992)
The course of cystoid macular oedema (CMO) following extracapsular cataract extraction with posterior chamber intraocular lens implantation was prospectively studied in 44 eyes of 44 consecutive diabetic patients without preoperative CMO. In 50% of eyes CMO was observed 6 weeks after surgery and in 25% was still present at 1 year. The preoperative presence of diabetic retinopathy significantly affected the postoperative onset and persistence of CMO. CMO occurred postoperatively in only 32% of eyes without pre-existing diabetic retinopathy and in 81% of eyes with pre-existing diabetic retinopathy (p < 0.05). CMO persisted at 1 year after surgery in only 7% of eyes without pre-existing diabetic retinopathy and in 56% of eyes in which diabetic retinopathy persisted (p < 0.01). Angiographic CMO (that is, detectable only on fluorescein angiography) was more common than clinical CMO (detectable on ophthalmoscopic examination as well) in eyes with no pre-existing diabetic retinopathy, whereas clinical CMO was seen more often than angiographic CMO when diabetic retinopathy was present preoperatively (p < 0.01). The course and final visual outcome of angiographic CMO were more favourable than in clinical CMO. Final visual acuity of at least 6/12 was achieved in 86% of eyes with angiographic CMO and in only 33% of eyes with clinical CMO. On the basis of the above findings we believe that cataract extraction should not be recommended for eyes with pre-existing diabetic retinopathy until the vision has deteriorated to at least 6/30-6/60.